Legal Updates to the Regional Police Criminal Investigation Unit's Standard Operating Procedures in Handling Online Fraud Crimes to Ensure Legal Certainty and Justice - Tri Satrio Sulistomo; Ahmad Redi (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
This study aims to analyze and reconstruct the operational standards of investigation by the General Criminal Investigation Unit of the Regional Police in handling online fraud crimes as part of legal reform efforts in Indonesia. The research method used is normative juridical with a statutory and conceptual approach, through a study of the Criminal Procedure Code, the Criminal Code, and Law Number 11 of 2008 concerning Electronic Information and Transactions, as amended by Law Number 1 of 2024 concerning Amendments to the ITE Law, as well as various relevant legal doctrines and literature. The results indicate that the existing legal construction has not been fully able to accommodate the characteristics of digital-based online fraud crimes, resulting in disharmony of norms, a lack of technical regulations, and irregularities in the implementation of investigations at the General Criminal Investigation Unit of the Regional Police. Empirical problems found include the lack of uniformity in standard operating procedures, limited investigator capacity in managing electronic evidence, obstacles to coordination with third parties, and jurisdictional constraints in cross-regional and cross-border cases. These conditions disrupt legal certainty and legal justice in the criminal justice system. Therefore, legal reform is needed through the reconstruction of operational standards for investigations that are adaptive to technological developments, strengthening the legitimacy of electronic evidence, harmonizing laws and regulations, and increasing institutional and human resource capacity. This study offers an ideal model for digital-based operational standards for investigations based on the principles of due process of law, legal certainty, and justice, in order to realize a law enforcement system that is effective, accountable, and responsive to the dynamics of modern crime.